Analysis of the Application of Arabic Language Environment in PPTQ Roudhlotul Jannah to Improve the al-Quran Memorization Ability of Students | Analisis Penerapan Lingkungan Berbahasa Arab di PPTQ Roudhlotul Jannah untuk Meningkatkan Kemampuan Hafalan al-Qur’an Santri - Azizah, Umi Nur; Nafisah, Jauharotun (An-nahdloh : Journal of Arabic Teaching, 2024)
This research examines the influence of the Arabic language environment at the Tahafudzul Qur'an Roudhlotul Jannah Kedaton 1 Islamic Boarding School, Batanghari Nuban District, East Lampung Regency, Lampung Province, to improve female students' ability to memorize the Qur'an, using analysis. The aim of this research is to analyze whether or not there is an influence from the Arabic language environment for students at the Tahafudzul Quran Roudhlotul Jannah Islamic Boarding School, East Lampung. This research is descriptive-qualitative research with the type of field research. With this research, it will certainly be easier and happier for students to implement the Arabic language environment because it has an influence on memorizing the al-Qur'an.